TEACHERS' STRATEGIES IN DEVELOPING EARLY LITERACY SKILLS OF CHILDREN AGED 5-6 YEARS AT AL-AMIN GAGAH KADUR KINDERGARTEN PAMEKASAN - Nisa', Miladia Khoirun; Reswari,, Ardhana (Universitas Al-Hikmah Indonesia, 2024)
The purpose of this study is to find out the strategies carried out by teachers in developing the literacy skills of children aged 5-6 years at Al-Amin Gagah Kadur Kindergarten, the impact and supporting and inhibiting factors of teachers in implementing strategies to develop early literacy skills. The method carried out in this study is to use a qualitative method with a descriptive approach. The qualitative method is to describe the characteristics of a phenomenon with a narrative description. Data collection in this method is through observation techniques, interviews, and documentation, then the data obtained is analyzed using triangulation techniques and source triangulation and described through words. The results of the study show that teachers at Al-Amin Gagah Kadur Kindergarten Pamekasan use several strategies to develop early literacy skills, including: geometric letter cards, lego, finger painting, hijaiyah letter collages, letter stamps. The impact of the strategy carried out is: increasing children's literacy ability, children more easily understand the lesson, with the design of an interesting and appropriate strategy, it can help in achieving the goals of the learning plan to be achieved, increase the attractiveness of children's learning, help children recognize letters and letter symbols. The obstacles in the implementation of the strategy are: lack of participation from some different parents and the attitude of parents who are too much to delegate responsibility to the teacher, the diversity of children's emotional conditions at school, children lack focus in learning, loss of children's confidence. The supporting factors are: The availability of media that supports and utilizes existing media, educators who are always enthusiastic and trying to give their best, the existence of new people.